Evaluation Of The Effectiveness of The Subsidized Fertilizer Distribution System In Bulukumba Regency - Rasdiana Mudatsir; Sitti Arwati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
The distribution of subsidized fertilizer plays an important role in supporting agricultural productivity and food security in Indonesia. This study aims to evaluate the effectiveness of subsidized fertilizer distribution among rice farmers in Jojjolo Village, Bulukumba District, based on five key indicators: type, quantity, location, price, and timing. The research employs a descriptive quantitative approach with data collection techniques including questionnaires, in-depth interviews, field observations, and administrative documentation. The sample consisted of 23 farmers actively involved in the fertilizer subsidy program. The results showed that the distribution of subsidized fertilizer was fairly effective, with an average effectiveness score of 73.06%. Accuracy in type and location demonstrated the highest performance, at 91.3% and 87%, respectively, indicating that the RDKK-based needs planning system is functioning reasonably well. However, price accuracy (60.9%) and timing accuracy (52.2%) remain low, indicating challenges in price monitoring and distribution logistics efficiency. These gaps align with previous studies highlighting infrastructure issues, limited information technology, and weak coordination within the supply chain. This study concludes that while the distribution system demonstrates relatively good performance in some areas, improvements are still needed in logistics systems, price monitoring, and the utilization of digital technology. These findings provide important insights into agricultural input distribution in remote areas and serve as a foundation for future policy improvements.